Heurísticas para mapeamento de redes virtuais de sincronia híbrida - Oliveira , Rômulo Reis de (2015)
Hybrid synchrony virtual networks arose by combining network virtualization, which allows the co-existence of several virtual networks in the same shared physical substrate, providing infrastructure in a flexible and economic way, with partial synchrony network architecture, which is relevant in distributed systems in order to build reliable systems. One of the main challenges in network virtualization is the efficient mapping of virtual resources in the substrate network, since it is a NP-Hard complexity problem. When considering the synchrony of virtual and physical resources it becomes more difficult to map, making it unfeasible to calculate the optimal solution in real environments. Thus, heuristic approaches are necessary for finding semi-optimal solutions faster. In this work, four heuristics for mapping hybrid synchrony virtual networks are adapted. In order to evaluate these heuristics, two sets of experiments were executed. In the first set is compared the optimal solutions with their respective semi-optimal solutions, the results show the heuristics’ efficiency are better when the virtual network requests are smaller, furthermore there were some semi-optimal solution mapping costs equivalent to the optimal solution mapping cost. The second set of experiments evaluates the heuristics performance using a physical substrate closer to real context and a larger number of virtual network requests. The results of this second set of experiments demonstrate that even with a larger number of virtual requests and a larger substrate, the solutions were computed in acceptable time.